An invasive amphibian drives antipredator responses in two prey at different trophic positions. (21st April 2020) - Secondi, Jean; Raux, Fanny
Abstract: Generalist invasive predators consume prey at different trophic levels and generate drastic changes in local communities. However, the long-term effects of predation may be reduced by eco-evolutionary responses of native populations. The capacity of prey species distributed across the trophic network to develop antipredator responses may determine the ecosystem potential to buffer against the invader. The African clawed frog is a major invader on several continents. Because of its large size, generalist diet, and aquatic lifestyle, we predicted the development of antipredator responses in prey species at different trophic levels. We tested for behavioral shifts between populations within and outside the invasive range in the herbivorous snail Physella acuta and the predatory heteropteran, the backswimmer Notonecta glauca . We detected antipredator responses in both prey species. In sympatry, P. acuta stayed higher in the water column, while N. glauca spent more time swimming underwater and less time surfacing when the predator cues were present. In allopatry, P. acuta dived deeper and N. glauca spent more time surfacing and stayed longer still underwater. In both species, sympatric populations showed evidence of olfactory recognition of the frog. Our results show that the introduction of a top predator like Xenopus laevis in the pond ecosystem drives behavioral antipredator responses in species across the trophic network. Eco-evolutionary processes may allow some degree of long-term resilience of pond communities to the invasion of X. laevis . Abstract : Introduced predators consume native prey and threaten local ecosystems when they become invasive. We showed that two native prey occupying different niches in the pond ecosystem, an herbivorous snail and a predatory insect, developed behavioral avoidance of the African clawed frog. Predator olfactory cues were sufficient to change prey behavior. The rapid development of responses in multiple species may contribute to reduce the impact of the invader in this ecosystem.